2008
DOI: 10.1007/s00392-008-0721-2
|View full text |Cite
|
Sign up to set email alerts
|

Athlete’s heart or hypertrophic cardiomyopathy?

Abstract: Intensive endurance training is able to cause a distinct pattern of functional and structural changes of the cardiovascular system. In an unknown proportion of athletes a so called "athlete's heart" develops. There is an overlap between this type of physiologic cardiac hypertrophy and mild forms of hypertrophic cardiomyopathy (HCM), the most common genetic disorder of the cardiovascular system with a prevalence of 0.2%. HCM is caused by mutations in 14 genes coding for sarcomere proteins. In the literature up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 37 publications
2
37
1
8
Order By: Relevance
“…2a). Previous research has shown that individuals diagnosed with HCM demonstrated diastolic dysfunction [5,21], and it is suggested that this can be differentiated from those individuals that have physiological hypertrophy resulting from exercise training [21,44,51,52]. In Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2a). Previous research has shown that individuals diagnosed with HCM demonstrated diastolic dysfunction [5,21], and it is suggested that this can be differentiated from those individuals that have physiological hypertrophy resulting from exercise training [21,44,51,52]. In Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The Echo data support the BCG observations. Lauschke and co-workers have suggested that changes in diastolic function maybe important to help clarify differences between the "athletic" and "pathological" heart [54], and thus warrants further investigation. This study advances our understanding of HCM, but more detailed studies comparing Echo, cardiac MRI and BCG are required to confirm the sensitivity and specificity of the BCG in detecting cardiac anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, physiological and pathological forms of hypertrophy are differentiated using a variety of diagnostic algorithms and echocardiography. 2,3 However, uncertainty frequently persists and physicians are frequently turning to cardiovascular magnetic resonance (CMR) to resolve such cases. This technique offers superior spatial resolution, better visualization of the lateral wall, and apex and is unlimited by echocardiographic windows; however, a normal range for wall thickness measurements is lacking and the echo cutoff of 13 mm is frequently used.…”
mentioning
confidence: 99%
“…4 With the development of modern UCG and other imaging examining methods, these changes were further revealed and confirmed. In 1975, Morganroth 5 and fellow researchers first found evidence of a thickened LV wall, increased weight, and end-diastolic volume of the left ventricle in athletes by UCG.…”
Section: Discussionmentioning
confidence: 90%